Phylogenetic relationships of Scelimeninae genera (Orthoptera: Tetrigoidea) based on COI, 16S rRNA and 18S rRNA gene sequences - Chen, Ya-Zhen; Deng, Wei-An; Wang, Jia-Min; Lin, Li-Liang; Zhou, Shan-Yi (Zootaxa, 2018)
Scelimeninae is an important subfamily of Tetrigoidea; however, the phylogenetic relationships within Scelimeninae are poorly understood, and its generic classification has remained unstable. In this study, the COI, 16S rRNA and 18S rRNA genes from 24 species in 9 genera within Scelimeninae were amplified and sequenced, the base composition and inter-species genetic distance of the combined sequence of COI, 16S rRNA and 18S rRNA genes were analyzed, and the molecular phylogenetic relationships were reconstructed using Maximum Likelihood (ML) and Bayesian inference (BI) methods. The results of sequence analysis showed that the total length of the combined COI, 16S rRNA and 18S rRNA gene sequence was 3507 bp, including 2345 conservative sites, 1144 variable sites and 901 parsimony-informative sites. The average A+T content was 63.5% and 78.1% in the COI, 16S rRNA sequences, respectively, indicating A+T bias. The average genetic distance between all species was 0.134, and the average genetic distance in the inner group (Scelimeninae) was 0.126. A phylogenetic tree based on the combined sequences of the COI, 16S rRNA and 18S rRNA genes showed that the phylogenetic relationships among 9 Scelimeninae genera were as follows: Criotettix + (((Zhengitettix + Hebarditettix) + (Falconius + (Scelimena + Paragavialidium))) + ((Eucriotettix + Thoradonta) + Loxilobus)). The molecular phylogenetic results generally support the morphological taxonomy; at the genus level, Criotettix, Scelimena, Paragavialidium, Thoradonta and Eucriotettix are monophyletic groups, Scelimena and Paragavialidium form sister groups, and Thoradonta and Eucriotettix also form sister groups, but the relationship between Hebarditettix and Zhengitettix needs further study. At the species level, synonyms may exist between Thoradonta spiculoba and Thoradonta transpicula and Thoradonta nodulosa and Thoradonta obtusilobata, but more studies are required to confirm this inference.